Salivary biomarkers in cancer - A narrative review - R. Swaathi; Madhu Narayan; Rajkumar Krishnan (Oral Oncology Reports)
Cancer remains as the most persistent disease among human population and is one of the leading causes of morbidity and mortality worldwide. The effective treatment is related to not only the right selection of therapy but also dependent on early diagnosis. The biomolecular breakthroughs of the neoplastic process have aided knowledge in this tumor mechanism and early diagnosis substantially enhances the odds of effective therapy. The hunt for novel biomarkers may help in the early identification of this disease. Antibodies, microorganisms, Deoxyribonucleic acid (DNA), Ribonucleic acid (RNA), lipids, metabolites and proteins are some of the many types of biomarkers. Biofluid is defined as ''a liquid/mixture of various molecules generated by living organisms, e.g., saliva, urine, serum, blood, interstitial fluid, plasma, cytosol, etc.,'' Saliva is the most cost-effective, least intrusive, non-coagulated and safest biofluid for use in clinical diagnostics. Saliva contains a diverse array of proteins/peptides, nucleic acids, electrolytes, and hormones derived from a variety of local and systemic sources. It appears that these found in the salivary fluid might be used as tumor biomarkers. This exhaustive review article describes in detail about the advantages of using saliva as a diagnostic medium, method of saliva collection and storage and the various salivary biomarkers which can be used in the diagnosis of cancer, both local and distant.